Size Distributions of Water-Soluble Inorganic Ions in Atmospheric Aerosols During the Meiyu Period in the Yangtze River Delta, China - Wu, Zhaoye; Liu, Duanyang; Zhao, Tianliang; Su, Yan; Zhou, Bin (Frontiers in Environmental Science, 2021)
In order to investigate the chemical composition distributions and pollution characteristics of Total water-soluble inorganic ions (TWSII) in the rain period (Meiyu) in the East Asian summer monsoon season, including the impact of Meiyu on air pollution in the Yangtze River Delta, East China, the gaseous pollutant concentrations, the 9 sizes segregated particles, and water-soluble inorganic ions of aerosols were measured on the north shore of Taihu Lake from June 4 to July 5, 2016. Results show that the mass concentrations of atmospheric particulate matters (PM2.5 and PM10) and main gaseous pollutants (SO2, NO2, CO, and O3) decrease during the Meiyu period, with the largest decline in PM10 and the smallest in CO. TWSII in atmospheric particles are mainly concentrated in fine particles during the Meiyu period. The values of ρ (TWSII) for PM1.1, PM1.1–2.1, and PM2.1–10 before the Meiyu onset are generally greater than those during the Meiyu period. During the first pollution process, the ρ(TWSII) for PM1.1 and PM1.1–2.1 first increase to the peak values, and then decrease during the moderate rainfall period, when the ρ(TWSII) in PM2.1–10 increase to its maximum before the Meiyu onset. The mass concentrations for anions, cations, and total ions at different particle-size sections all exhibit bimodal distributions before and after the Meiyu onset. The mass concentration peaks at a particle size of 1.1–2.1 μm for fine particles, while at 5.8–9.0 μm (before the Meiyu onset) and 9.0–10.0 μm (during the Meiyu period) for coarse particles, respectively. The peak particle size for mass concentration of coarse particles moves toward larger sizes during the Meiyu period. The mass concentrations of SO42− at different particle-size sections show a bimodal distribution before the Meiyu onset and a multi-modal distribution during the Meiyu period. The mass concentrations of NO3− at different particle-size sections show a bimodal distribution before the Meiyu onset and a unimodal distribution during the Meiyu period. The mass concentrations of NH4+ at different particle-size sections present a bimodal distribution before and after the Meiyu onset, with the particle-size for peak concentrations distributing in 1.1–2.1 and 5.8–9.0 μm before the Meiyu onset, and 9.0–10.0 μm during the Meiyu period. The mean value of nitrogen oxidation ratio (NOR) is higher before the Meiyu onset than after, indicating that the secondary conversion of NO2 before the Meiyu onset is enhanced. The sulfur oxidation ratio (SOR) values are greater than NOR values, but the concentrations of NO2 in the same period during the Meiyu period are higher than those of SO2, which indicates that the secondary conversion of SO2 during the Meiyu period on the north bank of Taihu Lake is stronger than that of NO2. During the whole observation, the contribution of stationary sources mainly contributed to the atmospheric particulate matters during the Meiyu period. The contributions of vehicle exhaust and coal combustion to fine particles are more obviously affected by the changes in meteorological conditions during the Meiyu period, and the vehicle emissions contribute more to PM1.1–2.1 than to PM1.1.